Comparison of bacteria-based autonomous and autogenous healing performances of geopolymer mortar exposed to sulfate attack - Tanyildizi, Harun; Ziada, Mahmoud; Uysal, Mucteba; Coskun, Ahmet (Wiley, 2025)
In this study, the performances of bacteria-based autogenous and autonomous healing of metakaolin, red mud, and colemanite-based geopolymer mortar exposed to sulfate attack were compared. The red mud and colemanite in geopolymer mortar mixtures were used at 0%, 6%, and 4% of metakaolin by weight. Bacteria-free samples for autonomous healing and bacteria-containing samples for autogenous healing were produced. S. pasteurii was used as the bacteria in this study. Then, these specimens were exposed to sulfate attack for periods of 1, 2, 3, 6, and 12 months. After the samples were exposed to sulfate attack, the autogenous and autonomous healing process was carried out. In the healing process, a solution containing 9 x 108 cells/ml bacteria (Bac-media) was injected into the cracks with a syringe to heal the geopolymer mortar samples. The mass change, length change, compressive strength, ultrasonic pulse velocity, flexural strength, and capillary water absorption tests of autonomous and autogenous healing geopolymer mortar samples were performed. Also, SEM/EDS, FTIR, Micro-computed tomography (Micro CT), and XRD were carried out for microstructure analysis. This study found that the mechanical properties of autonomous healing samples were higher than those of autogenous healing samples. Also, Micro-CT analysis found that 98.51% of the total porosity of the geopolymer mortar exposed to the sulfate attack was filled with CaCO3 precipitated by using S. pasteurii. These results provide an effective method for the recovery of geopolymer composites subjected to durability effects such as sulfate attack.
Keywords: autogenous healing; autonomous healing; colemanite; geopolymer mortar; metakaolin; red mud; sulfate attack